Biomaterial Substrate‐Mediated Multicellular Spheroid Formation and Their Applications in Tissue Engineering. Issue 12 (9th October 2017) - Tseng, Ting‐Chen; Wong, Chui‐Wei; Hsieh, Fu‐Yu; Hsu, Shan‐hui
Abstract : Three‐dimentional (3D) multicellular aggregates (spheroids), compared to the traditional 2D monolayer cultured cells, are physiologically more similar to the cells in vivo. So far there are various techniques to generate 3D spheroids. Spheroids obtained from different methods have already been applied to regenerative medicine or cancer research. Among the cell spheroids created by different methods, the substrate‐derived spheroids and their forming mechanism are unique. This review focuses on the formation of biomaterial substrate‐mediated multicellular spheroids and their applications in tissue engineering and tumor models. First, the authors will describe the special chitosan substrate‐derived mesenchymal stem cell (MSC) spheroids and their greater regenerative capacities in various tissues. Second, the authors will describe tumor spheroids derived on chitosan and hyaluronan substrates, which serve as a simple in vitro platform to study 3D tumor models or to perform cancer drug screening. Finally, the authors will mention the self‐assembly process for substrate‐derived multiple cell spheroids (co‐spheroids), which may recapitulate the heterotypic cell–cell interaction for co‐cultured cells or crosstalk between different types of cells. These unique multicellular mono‐spheroids or co‐spheroids represent a category of 3D cell culture with advantages of biomimetic cell–cell interaction, better functionalities, and imaging possibilities. Abstract : Three‐dimentional (3D) multicellular aggregates (spheroids) are physiologically more similar to the cells in vivo. This review focuses on biomaterial substrate‐derived multicellular spheroids and their applications in tissue engineering and tumor models. These unique multicellular mono‐spheroids or co‐spheroids represent a category of 3D cell culture with advantages of biomimetic cell–cell interaction, better functionalities, and imaging possibilities. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visitwww.afob.org .